Faktor-faktor yang mempengaruhi kinerja rantai pasok pada bisnis kuliner di Kota Yogyakarta - Rahmad, Nuraini; Fatliana, Anggun Nindy; Nasirly, Riri; Larasati, Tengku Indira (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The development of the Indonesian economy is inseparable from the role of the business industry in various regions spread throughout Indonesia. Yogyakarta City is a city with good potential for the business industry and MSMEs because it is supported by the tourism and education sectors. One of them is the culinary business. However, like other business fields, the culinary business is also not free from problems in carrying out supply chain management. The study aims to see the effect of Integration, Information Sharing, Long Term Relationship, Agility, and Responsiveness on SCM performance. The sample used was 30 respondents of meatball culinary business owners or employees in the city of Yogyakarta. Data analysis techniques using Multiple Linear Regression. The results showed that the variables of Integration, Information Sharing, Long Term Relationship, Agility have a positive and significant effect on SCM performance, while the Responsiveness variable has no significant effect on SCM performance. All variables are simultaneously significant between integration, information sharing, long term relationship, agility, and responsiveness to SCM performance.